Next Steps for Elevating Health on Trade and Investment Policy Agendas; Comment on "How Neoliberalism Is Shaping the Supply of Unhealthy Commodities and What This Means for NCD Prevention" - Belinda Townsend (Kerman University of Medical Sciences, 2020)
Despite intergovernmental calls for greater policy coherence to tackle rising non-communicable diseases (NCDs), there has been a striking lack of coherence internationally and nationally between trade and health sectors. In this commentary, I explore the arguments by Lenucha and Thow in relation to barriers for greater coherence for NCDs, apply them to regional trade agreements, and point to next steps in research and advocacy for greater attention to health and NCD prevention in government trade agendas.